Urgensi Pembentukan Komisi Nasional Disabilitas Dalam Pengawasan Fasilitas Perpustakaan Bagi Difabel - Moh Rosyid (IAIN Ponorogo, 2020)
The purpose of writing is analyzing the needs to be formed immediately National Commision Disability by the state. The effect has not yet been formed, constitution implementation not well implemented by organizer library, government offices and campus library in Kudus city, central Java. The data are obtained from literature review of written materials on library and Law No 8 of 2016 on People with Disabilities, Law No 14 of 2008 on the Openness of Public Information, and Law No 43 of 2017 onLibraries. Data were analyzed in descriptive qualitative method. Library as a public space should provide facilities people with disabilities. However, the implementation of the Law on People with Disability is difficult because the supporting instruments including 8 government regulations (PP), 2 presidential regulations (Perpres), Minister of Social affairs; regulation (Permensos), and the National Disability Commission has not yet been realized. Once the supporting regulations are established, then the Openness of Public Information Act is also implemented. It is our task to guard the establishment of the Laws and regulations. National Commission Disability urgently formed.